2015
DOI: 10.1080/11956860.2015.1079409
|View full text |Cite
|
Sign up to set email alerts
|

Long-term decline in a salt marsh hare population largely driven by bottom-up factors

Abstract: The widespread decline of the European brown hare (Lepus europaeus) in Europe has been attributed to both bottom-up and top-down factors, as well as climate change. Few studies have attempted to study the relative importance of these factors considered simultaneously. In this study we tested the hypotheses that hare population density is regulated by bottom-up (food), top-down (predation) or abiotic factors including tidal floods and climatic conditions. We related data on hare population density on a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…atherica also spread at the cost of low-statured species such as Puccinellia maritima and Festuca rubra [ 45 ]. The reduction of these edible plant species initially resulted in a decline of winter-staging Brent geese Brant bernicla [ 17 ], followed by a decrease in European brown hares Lepus europaeus [ 72 ]. Similarly to these studies, we observed a reduction in Greylag goose numbers that co-occurred with an increase in E .…”
Section: Discussionmentioning
confidence: 99%
“…atherica also spread at the cost of low-statured species such as Puccinellia maritima and Festuca rubra [ 45 ]. The reduction of these edible plant species initially resulted in a decline of winter-staging Brent geese Brant bernicla [ 17 ], followed by a decrease in European brown hares Lepus europaeus [ 72 ]. Similarly to these studies, we observed a reduction in Greylag goose numbers that co-occurred with an increase in E .…”
Section: Discussionmentioning
confidence: 99%
“…The eastern part of the saltmarsh (the study area) is only grazed by small herbivores, including spring staging Brent Geese ( Branta bernicla ), Barnacle Geese ( Branta leucopsis ), and year‐round present Brown hares ( Lepus europaeus ) and rabbits ( Oryctolagus cunniculus ). Hares and geese are the most important herbivores, while predators are rare in this system (Van De Koppel et al, ; Kuijper & Bakker, ; Schrama et al, ; Wal, Egas, et al, ; Van Der Wal et al, ). A natural successional gradient is present here, as the island expands naturally eastward (Olff et al, ): the eastern part of the island is younger than the western part, and different successional stages occur adjacent to one another, naturally separated by creeks (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of small herbivores on plant diversity may change along successional gradients. Small herbivores are usually selective grazers (Olff & Ritchie, ), and thus, changes in the identity of forage plants during vegetation succession may change the abundance of herbivores, particularly in systems where predators are rare (Schrama, Kuijper, Veeneklaas, & Bakker, ). The abundance of herbivores is sometimes, if not always, more important than herbivore size in regulating plant communities (Olofsson, Hulme, Oksanen, & Suominen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivore feeding preferences can affect plant performance and vegetation structure (Furbish & Albano 1994; Kuijper & Bakker 2008), and abiotic or biotic context can influence consumer pressure. For example, environmental stress can reduce forage quality or abundance, or predators can keep herbivores in check (Silliman & Bertness 2002; Crain 2008; Schrama et al 2015). Abiotic factors have long been considered the primary constraint on plant performance and community structure in salt marsh, but herbivore impacts have also been documented (Kotanen & Jefferies 1997; He & Silliman 2016).…”
Section: Discussionmentioning
confidence: 99%